Experimental and numerical study of air flow and temperature variations in an electric vehicle cabin during cooling and heating. (5th June 2018) - Mao, Yiyi; Wang, Ji; Li, Junming
Highlights: The numerical results agreed well with the experiments. The vehicle motion increased the thermal losses and gains from the cabin. The thermal stored in the seat strongly affects the air temperature variations. The highest velocities were near the inlets and outlets of the computational domain. Abstract: A series of experiments was conducted in an electric vehicle with four occupants while parked or being driven in the winter and the summer. The air and surface temperatures in the vehicle cabin and the heat fluxes on different closure surfaces were measured during the cooling and heating periods. With the temperature were then modeled in a transient numerical simulation of the electric vehicle cabin the air flow and temperature variations inside the cabin analyzed for the same conditions as in the experiments. The numerical model accurately predicted the temperature variations with differences of less than 10% compared with the experimental data. Analysis of the air temperature and velocity distributions from the transient model showed that the thermal storage in the seat significantly affected the thermal comfort adjustments for the transient conditions. The vehicle movement increased the convective heat transfer at the outer surface of the cabin, which increased the heat transfer between the outside and the inside air and extended the time to adjust the thermal comfort.